A potential integral equations method for electromagnetic scattering by penetrable bodies. - De Doncker, P. (IEEE Transactions on antennas and propagation)
A method for computing the electromagnetic scattering by general inhomogeneous penetrable bodies is presented. The method is based on the volume equivalence principle and it uses the electromagnetic potentials as unknowns. The resulting coupled integral equations system is solved by the method of moments in combination with cubical and curvilinear meshes in the special case of purely dielectric scatterers. To show the accuracy of the method, numerical results of the transmitted and of the scattered fields are compared with existing analytical and experimental results